Leveraging UAV Technology in Local Geoid Modeling - Timilsina, Sushmita; Bhatt, Bhagirath (Journal of Land Management and Geomatics Education, 2025)
Leveraging UAV (Unmanned Aerial Vehicle) technology in local geoid modelling is a promising approach, particularly in areas with challenging terrain and sparse GNSS, leveling and gravity infrastructure. In this study, UAV was utilized to capture high-resolution images of the area surrounding the Land Management Training Centre (LMTC) from an altitude of about 120 meters. These aerial images were carefully georeferenced using a coordinate set of ellipsoidal height (h) and orthometric height (H). A sufficient number of points were then generated from these images, which included both ellipsoidal and orthometric height data. The next step involved calculating the geoid height (N). This calculation provided the point-specific geoid heights, which were then used to construct a comprehensive geoid model for the region. The evaluation of this geoid model was done by comparing it with the recent global gravity model. This assessment demonstrated that UAV technology can be useful for local geoid modeling, offering accurate and reliable data for understanding geoid variations on a local scale.